Предмет: Математика,
автор: Владушечка
Упростите выражение:
-6(9a+2b)+4(a-7b)
И решите уравнение:
5(2x-3)-2(3-2x)=15-6(x+1)
Ответы
Автор ответа:
0
- 6(9a + 2b) + 4(a - 7b) = - 54а - 12b + 4a - 28b = -50a - 40b
5(2x - 3) - 2(3 - 2x)=15 - 6(x +1)
10x - 15 - 6 + 4x = 15 - 6x - 6
10x + 4x + 6x = 15 - 6 + 6 +15
20x = 30
x= 30/20
x=3/2
x=1,5
5(2x - 3) - 2(3 - 2x)=15 - 6(x +1)
10x - 15 - 6 + 4x = 15 - 6x - 6
10x + 4x + 6x = 15 - 6 + 6 +15
20x = 30
x= 30/20
x=3/2
x=1,5
Автор ответа:
0
посмотри в
советую советую
советую советую
Похожие вопросы
Предмет: Информатика,
автор: Аноним
Предмет: Русский язык,
автор: Аноним
Предмет: История,
автор: gayrdima22
Предмет: Математика,
автор: egor2001november
Предмет: Физика,
автор: katerina2014458594